Effect of reynolds number on the dispersion of carbon black in natural rubber latex and filler–rubber interfacial interaction in high‐speed jet flow field. Issue 7 (3rd June 2013) - Han, Jingjie; Zhang, Yandan; Wu, Chifei; Ma, Yulu
<x xml:space="preserve">Abstract</x> A novel strategy of high‐speed impinging jet processing technique was developed to prepare rubber composites by directly mixing natural rubber latex (NRL) with carbon black (CB). The results showed that CB could be more evenly dispersed into natural rubber by jet compounding technique, compared with the traditional dry process. The dispersion of carbon black was improved at higher Reynolds number because of more intensive shear force. Furthermore, a high performance of natural rubber latex/CB composite was gained by jet compounding technique. When compared to the traditional dry process, the mechanical properties and abrasion resistance of the composite prepared by the jet compounding technique were greatly improved because of the improved filler–rubber interaction at higher Reynolds number. POLYM. COMPOS., 34:1071–1075, 2013. © 2013 Society of Plastics Engineers